PENGARUH EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Rani Rahmawati; Novera Martilova (CV. Adiba Aisha Amira, 2025)
A country's economic development cannot be separated from international trade, particularly through imports and exports, which is the driving force of this research. The government uses export and import policies to promote economic expansion. The aim of this research is to determine the influence of imports and exports on the economic growth of West Sumatra Province. This research uses quantitative methods. The data collection method is a time series from 1994 to 2023 obtained from the Central Statistics Agency of West Sumatra Province. The tests performed were multiple linear regression analysis, coefficient of determination test, t-test, f-test, normality test, autocorrelation test, heteroscedasticity test and multicollinearity test. The IBM SPSS Statistics version 27 program was used to process these data. The multiple linear regression analysis results in the equation: Y= 3003733.844 + 62.296X1 – 9.358X2. The constant value is 3003733.844. The t-test then shows that imports have no impact on economic growth, with a significant value (0.768 > 0.05) and the calculated t-value is smaller than the t-table (0.298 <2.5553). Exports have an effect if the calculated t-value is greater than the t-table (5.208 > 2.5553). Taken together, it shows that imports and exports have a large impact on value (0.000 < 0.05). With an R-squared value of 0.695, exports and imports are highly correlated with GDP growth of 69.5%. Meanwhile, factors not discussed in this study affect the remaining 30.5%.